Essence: Nguyen Trung, Tulip Duong, Ly Tran Quynh Giang, Nguyen Son, Do Hoang Tuong - KWOK, Kian Chow (Institutional Knowledge at Singapore Management University, 2018)
Discussions on works of the five Vietnamese artists in corresponding sections - Nguyen Trung: Between Worlds, Ly Tran Quynh Giang: Glimpses into the Closeted Identity, Tulip Duong: Art Books Under Her Bed, Nguyen Son: The Frozen Moment, Do Hoang Tuong: From Illustrator of Stories to Illustrator of Life.